Prevalence of fatty liver in type 2 Diabetic patients: Experience from northern Bangladesh (TAJ: Journal of Teachers Association, 2018)
This study was done to find out the prevalence of fatty liver in type2 Diabetic patients. This was a descriptive cross-sectional comparative study carried out in Department of Medicine, Rajshahi Medical College Hospital and Rajshahi Diabetic Association Hospital from July 2008 to June 2010. 100 (one hundred) diagnosed type2 diabetic patients were included. All of those study population were free from taking any hepatoxic drugs and free from any preexisting liver disease. This exclusion was done by history, through clinical examination and relevant investigations. Among 100 type2 diabetic patients, 66 (66%) had normal, 25 (25%) had mild fatty change, 6 (6%) had moderate fatty change in liver; 2 (2%) had mild hepatomegally and 1 (1%) had congested liver. Non had cirrhosis or hepatocellular carcinoma.TAJ 2014; 27(2): 11-13